Effectiveness of space spraying in combating Aedes aegypti populations in dengue-endemic areas - Kemmapon Chumchuen; Edward B McNeil; Theerakamol Pengsakul (Agriculture and Natural Resources, 2021)
Space spraying is a common vector control measure used to suppress Aedes aegypti mosquito populations during outbreaks of vector-borne diseases such as dengue. Space spraying can be conducted inside or outside the household or both. The current study assessed the effectiveness of space-spraying in reducing vector populations in an active endemic setting and determined factors associated with indoor spraying acceptability and indoor resting density based on the house density index (HDI) in Songkhla city, Thailand. Between September 2019 and January 2020, adult samples of both sexes of Ae. aegypti were collected from 35 households using insect sweep nets and aspirators within sprayed areas in response to ongoing dengue transmission at five time points: day 0 (the day before spraying), and then on days 1, 3, 5 and 7. An oral questionnaire was completed by an adult resident, and the outer premises of the households were inspected for water-holding containers. Attitude toward the effectiveness of indoor spraying was assessed among residents who received both indoor and outdoor spraying as a strategy to prevent dengue (n = 23) and those who only received outdoor spraying (n = 12). Linear regression analysis showed the HDI scores of mosquitoes on days 1, 3 and 5 were significantly lower than the baseline level in households that were sprayed indoors and outdoors. Associated factors for spraying effectiveness included the type of space spraying, the presence of stagnant water near the house and the adoption of preventive practices. The results suggested that the acceptability of indoor spraying was associated with the perception of the local community toward the effectiveness of indoor spraying. Local government campaigns should emphasize the difficulty in controlling Ae. aegypti mosquitoes and the need for both government and community action to improve coverage of space spraying and water/waste management during dengue outbreaks.